2019
DOI: 10.1111/petr.13359
|View full text |Cite
|
Sign up to set email alerts
|

Compassionate deactivation of ventricular assist devices in children: A survey of pediatric ventricular assist device clinicians’ perspectives and practices

Abstract: Objectives This study's objective was to investigate compassionate ventricular assist device deactivation (VADdeact) in children from the perspective of the pediatric heart failure provider. Background Pediatric VAD use is a standard therapy for advanced heart failure. Serious adverse events may affect relative benefit of continued support, leading to consideration of VADdeact. Perspectives and practices regarding VADdeact have been studied in adults but not in children. Methods A web‐based anonymous survey of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…The sample size is small with a 49% response rate, though the pediatric VAD community itself is relatively small and there was representation from centers across North America at varying sized programs. While response rate was moderate, it exceeds similar physician surveys in pediatric cardiology, with some surveys not reporting a response rate 10,30,31 . Multiple respondents per center were permitted; therefore, larger centers may be over‐represented in the survey results.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…The sample size is small with a 49% response rate, though the pediatric VAD community itself is relatively small and there was representation from centers across North America at varying sized programs. While response rate was moderate, it exceeds similar physician surveys in pediatric cardiology, with some surveys not reporting a response rate 10,30,31 . Multiple respondents per center were permitted; therefore, larger centers may be over‐represented in the survey results.…”
Section: Discussionmentioning
confidence: 92%
“…Only half of respondents reported discussing the possibility of compassionate deactivation in the setting of a devastating clinical event. Given the risk of mortality on device and high risk of adverse events, early and transparent dialogue with families is essential in providing compassionate end‐of‐life care as highlighted by several pediatric VAD reports and reviews 10,22‐26 . In terms of involvement of mature minors, while a majority of respondents reported involving them in the entire consent process, still 23% reported that not all risks were reviewed with them.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations